2022
DOI: 10.5194/acp-22-12093-2022
|View full text |Cite
|
Sign up to set email alerts
|

An improved representation of fire non-methane organic gases (NMOGs) in models: emissions to reactivity

Abstract: Abstract. Fires emit a substantial amount of non-methane organic gases (NMOGs), the atmospheric oxidation of which can contribute to ozone and secondary particulate matter formation. However, the abundance and reactivity of these fire NMOGs are uncertain and historically not well constrained. In this work, we expand the representation of fire NMOGs in a global chemical transport model, GEOS-Chem. We update emission factors to Andreae (2019) and the chemical mechanism to include recent aromatic and ethene and e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 98 publications
0
17
0
Order By: Relevance
“…Indeed, we found that GEOS-Chem tends to underestimate the HCHO enhancement in plumes older than 10 h (Figure a), which is likely due to the contribution from those missing fire VOCs, or inaccurate representation of the later-generation VOC degradation products. Expansion of VOC species in GEOS-Chem could improve the representation of VOC reactivity, and it is expected that the relative contributions of primary emissions to HCHO will be even smaller if we include more HCHO precursors. Hundreds of VOC species are known to be present in fire plumes, and many of them remain unidentified .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we found that GEOS-Chem tends to underestimate the HCHO enhancement in plumes older than 10 h (Figure a), which is likely due to the contribution from those missing fire VOCs, or inaccurate representation of the later-generation VOC degradation products. Expansion of VOC species in GEOS-Chem could improve the representation of VOC reactivity, and it is expected that the relative contributions of primary emissions to HCHO will be even smaller if we include more HCHO precursors. Hundreds of VOC species are known to be present in fire plumes, and many of them remain unidentified .…”
Section: Resultsmentioning
confidence: 99%
“…We distributed 35% biomass burning emissions in the first ten sigma layers above the boundary layer, and the other 65% within the boundary layer . The standard GEOS-Chem (v12.7.0) does not include biomass burning emissions and chemistry of ethene (C 2 H 4 ), but C 2 H 4 is a large contributor to organic reactivity in fire plumes . We incorporated the chemistry of C 2 H 4 following Kwon et al, and it has been incorporated in standard GEOS-Chem since version 13.3.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, CTMs only implement simplied chemistry for a handful (typically <30) of the most studied individual and lumped species, which were oen developed and evaluated for relatively well-studied environments such as urban areas, forests, and to a lesser extent the remote/clean troposphere. 24,30,[37][38][39][40] Recent work suggests the GEOS-Chem CTM underpredicts biogenic VOC reactivity ux by 40-60% in forest environments, with major uncertainties related to a few select known/modeled VOCs, rather than unrepresented species. 30 How well these modeled species represent the most important individual OH sinks in wildre smoke has yet to be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass burning (BB) is a major source of reactive organic carbon, both in the form of aerosol and non-methane organic gases (NMOG), to the atmosphere (Carter et al, 2022;Andreae et al, 1988;Yokelson et al, 2009;Akagi et al, 2013;Bond et al, 2004;Liu et al, 2016). BB emissions can have large impacts on air quality and climate across a range of scales, due both to primary species and to their transformation to secondary species such as ozone and secondary organic aerosol (SOA) (Cubison et al, 2011;Decarlo et al, 2010;Grieshop et al, 2009;Hennigan et al, 2011;Ortega et al, 2013;Tkacik et al, 2017;Yokelson et al, 2009;Hobbs et al, 2003;Akagi et al, 2013;Bourgeois et al, 2021;Hobbs et al, 1997;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%